The role of conversation analysis-informed instruction to enhance students' conversational skills in the Ethiopian context - Lemma Kassaye (Globe, 2020)
This study was aimed at developing conversational skills of first year students in the Department of English Language and Literature at Bahir Dar University using conversation analysis-informed intervention. A qualitative-conversation analysis (CA) approach was employed for the study in which a case study was used. Ten students were selected as participants in the study. The participants were provided with oral tasks before the intervention took place. The oral productions of the participants were recorded and analysed to identify their difficulties in terms of conversational skills. Based on the difficulties the participants had, they were taught conversational features to develop their knowledge and skills of conversational skills in the English language. The intervention took four months. In the post-intervention phase of the study, oral productions of the participants were also recorded using audio/video devices and analysed from the conversation analysis perspective to see the developments observed as a result of the CA based treatment. The findings showed that there were encouraging results with regard to the improvements of conversational skills of the study participants; their productions of successive and related expressions were observed to have improved. An increased use of conversational strategies and repairs in the post-intervention phase of the study is an evidence of the development of their conversational skills. The participants also developed their knowledge with regard to the use of spoken grammar in their conversations. Therefore, a CA based intervention has a great impact on the teaching of oral skills in English for it helps to identify students' learning difficulties and take pertinent actions.